PET-MRI for evaluation of response to radiochemotherapy in patients with locally advanced cervical cancer. Issue 5 (23rd February 2023) - Weyl, Ariane; Chollet, Charlotte; Gabiache, Erwan; Cancès-Lauwers, Valérie; Gallo, Franklin; Martinez, Alejandra; Courbon, Frederic; Leguevaque, Pierre; Brenot Rossi, Isabelle; Jalaguier, Aurélie; Lambaudie, Eric; Chantalat, Elodie; et al.
Abstract : Objective: We aimed to analyze the diagnostic test accuracy of positron emission tomography and a magnetic resonance imaging scan (PET-MRI) fusion in evaluating tumor response after radiochemotherapy in patients with locally advanced cervical cancer. Methods: Patients treated at two institutes between January 2008 and December 2016 were studied retrospectively. Re-evaluation by positron emission tomography (PET) and magnetic resonance imaging (MRI) was performed in a non-concurrent way 4–8 weeks after treatment. A nuclear medicine doctor and a radiologist (subsequently referred as "radiologists"), both experts in gynecological oncology, re-examined the post-treatment MRI and positron emission tomography–computed tomography (PET-CT) separately, and then performed a fusion of these examinations. In this study we describe this "a posteriori fusion methodology", with two levels, enabling limitation of anatomical shifts. The gold standard was anatomical pathology analysis of the surgical specimen, since all patients underwent surgery following this radiological re-evaluation. The radiologists' degree of certainty in their diagnoses, and the impact of fusion on their diagnostic confidence were assessed by the radiologists, using two Likert judgment scales. They also adjudicated on possible changes of interpretation after the fusion. Results: Thirty-one patients were included. The PET-MRI fusion has a sensitivity of 79% and a specificity of 90%. The positive predictive value (PPV) was 94%, and the negative predictive value (NPV) was 69%. In 45% of cases (n=13), radiologists reported an improvement in their degree of certainty in their diagnosis using a Likert judgment scale, due to inspecting the PET and MRI fused. A change in interpretation of tumor response was observed using a Likert judgment scale in 31% of cases. Conclusion: PET-MRI fusion improves the radiologist's own diagnostic confidence in assessing response to concurrent radiochemotherapy in locally advanced cervical cancer. More studies using a latest generation hybrid system will be necessary to further compare to MRI and PET-CT.